2016
DOI: 10.1093/pm/pnw190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repetitive Intracutaneous Injections with Local Anesthetics and Steroids for Acute Thoracic Herpes Zoster and Incidence of Postherpetic Neuralgia

Abstract: Repetitive intracutaneous injections with local anesthetics and steroids along with standard treatment significantly reduce the duration of pain and herpetic eruption and incidence of PHN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…The main reason for PHN has been shown to be ongoing painful signal input during the acute inflammatory phase, which causes central nervous system changes that generate chronic pain (20). Recently, attempts to reduce the incidence of PHN have been bolstered by the findings of clinical trials that anticonvulsants, opioid analgesics, tricyclic antidepressants, or nerve blocks are effective treatments for HZ (21)(22)(23). However, it remains unknown when supplemental pain managements should be started.…”
Section: Wwwpainphysicianjournalcom Discussionmentioning
confidence: 99%
“…The main reason for PHN has been shown to be ongoing painful signal input during the acute inflammatory phase, which causes central nervous system changes that generate chronic pain (20). Recently, attempts to reduce the incidence of PHN have been bolstered by the findings of clinical trials that anticonvulsants, opioid analgesics, tricyclic antidepressants, or nerve blocks are effective treatments for HZ (21)(22)(23). However, it remains unknown when supplemental pain managements should be started.…”
Section: Wwwpainphysicianjournalcom Discussionmentioning
confidence: 99%
“…Intracutaneously injecting a mixture of local anesthetics and/or steroid has been implicated in controlling hyperalgesia in in previous clinical studies. [ 13 15 ] We recently reported that intracutaneous injection of local anesthetics and steroids was a useful interventional strategy to potently control acute thoracic herpes zoster pain. [ 13 ] In the present study, we further found that intracutaneous injection of local anesthetics and steroids was also effective to alleviate acute neck pain, by using oral ibuprofen as a positive control.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 15 ] We recently reported that intracutaneous injection of local anesthetics and steroids was a useful interventional strategy to potently control acute thoracic herpes zoster pain. [ 13 ] In the present study, we further found that intracutaneous injection of local anesthetics and steroids was also effective to alleviate acute neck pain, by using oral ibuprofen as a positive control. Together with this study, we believe that intracutaneous injection of local anesthetics and steroids can be a novel strategy for different kinds of acute pain control, and our future study will employ and generalize this treatment in acute pain management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations